Advertisement Remove all ads

Simplify the Following Expressions: (5 + Sqrt7)(5 - Sqrt7) - Mathematics

Simplify the following expressions:

`(5 + sqrt7)(5 - sqrt7)`

Advertisement Remove all ads

Solution

We know that `(a + b)(a - b) = a^2 - b^2`We will use this property to simplify the expression

`(5 + sqrt7)(5 - sqrt7)`

`:. (5 + sqrt7)(5 - sqrt7) = 5^2 - (sqrt7)^2`

`= 5 xx 5 - sqrt7 xx sqrt7`

`25 - sqrt(7 xx 7)`

`= 25 - (7^2)^(1/2)`

`= 25 - 7^1`

= 18

Hence the value of expression is 18.

  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

RD Sharma Mathematics for Class 9
Chapter 3 Rationalisation
Exercise 3.1 | Q 3.2 | Page 2
Advertisement Remove all ads

Video TutorialsVIEW ALL [1]

Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×